Предмет: Алгебра, автор: tankto1122

сделайте пожалуйста​

Приложения:

Ответы

Автор ответа: сок111213
1

 \frac{5x}{2a}  +  \frac{3x}{2a}  =  \frac{5x + 3x}{2a}  =  \frac{8x}{2a}  =  \frac{4x}{a}

 \frac{a + b}{12}  -  \frac{a - 5b}{12}  =  \frac{a + b -( a - 5b)}{12}  = \frac{a + b  - a  +  5b}{12} =  \frac{6b}{12}  =  \frac{b}{2}

 \frac{b - 3}{5}  +  \frac{13 - b}{5}  =  \frac{b - 3 + 13 - b}{5}  =  \frac{10}{5}  = 2

 \frac{a + 2b}{8}  +  \frac{3a + 6b}{8}  =  \frac{a + 2b + 3a + 6b}{8}  =  \frac{4a + 8b}{8}  =  \frac{4(a + 2b)}{8}  =  \frac{a + 2b}{2}

 \frac{6m - 3}{10m}  -  \frac{m - 13}{10m}  =  \frac{6m - 3 - (m - 13)}{10m}  =  \frac{6m - 3 - m + 13}{10m}  = \frac{5m + 10}{10m}  =  \frac{5(m + 2)}{10m}  =  \frac{m + 2}{2m}

 \frac{5x - 3}{4x}  +  \frac{11 - x}{4x}  =  \frac{5x - 3 + 11  - x}{4x}  =  \frac{4x +8 }{4 {}x }  =  \frac{4(x + 2)}{4x}  =  \frac{x + 2}{x}

Похожие вопросы
Предмет: Українська мова, автор: dianamostovik